Akses Informasi dan Pengetahuan Stunting pada Remaja Putri - Eva Yunitasari; Feni Elda Fitri; Dayana Noprida (JURNAL WACANA KESEHATAN, 2026)
Stunting is a growth and development disorder in children caused by chronic malnutrition and repeated infections, characterized by height below the age standard (height-for-age < -2 SD). In efforts to prevent stunting, adolescent girls need special attention because they are future mothers who will play a role in giving birth to the next generation. The purpose of this study is to determine the relationship between information exposure and knowledge of stunting among adolescent girls. This research is a quantitative study with a cross-sectional design conducted at SMA Negeri 2 Kalianda with a population of 1,521 female students. The sampling technique used was purposive sampling, resulting in 510 respondents. Data analysis was conducted univariately to describe the frequency distribution of each variable, and bivariately using the chi-square test. Out of a total of 510 respondents, in the group that had not been exposed to stunting information, there were 12 respondents (60%) with poor knowledge, while in the group that had been exposed, there were 8 respondents (40%). In the adequate knowledge category, 120 respondents (63.5%) had not been exposed to information and 69 respondents (36.5%) had been exposed. Meanwhile, in the good knowledge category, 124 respondents (41.2%) had not been exposed to information and 177 respondents (58.8%) had been exposed. The results of the chi-square test showed a p-value of 0.001 (p<0.05), indicating a significant relationship between exposure to stunting information and the respondents' level of knowledge. It is recommended that schools and healthcare workers enhance the dissemination of information and education about stunting thru engaging and sustainable media to improve the knowledge of adolescent girls.